The Determinant of Performance Accountability in Banten Province During Covid-19 Pandemic - Ratu Heti Suryawiati; Elvin Bastian; Windu Mulyasari (Journal of Applied Business, Taxation and Economics Research, 2022)
This research aims to determine the effect of the public sector management control system, organizational culture, and reporting system on performance accountability and the role of competence of state civil servants in moderating public sector management control systems, organizational culture, and reporting systems on performance accountability during the Covid-19 pandemic. in the Regional Apparatus Organization (OPD) of Banten Province. This research uses primary data with the purposive sampling method. The object of research is in the OPD of Banten Province with a sample of 75 State Civil Apparatus in fifteen (15) OPD. The data analysis technique used is Structural Equation Modeling (SEM) analysis with the Warp PLS version 7.0.The results of this study indicate that the public sector management control system and organizational culture have a positive effect on performance accountability, while the reporting system does not affect performance accountability. Meanwhile, the competence of the state civil apparatus failed to moderate the public sector management control system for performance accountability. However, the competence of state civil servants has succeeded in moderating organizational culture and reporting systems for performance accountability.